An exceptionally preserved myodocopid ostracod from the Silurian of Herefordshire, UK. - Siveter, D; Briggs, D; Siveter, D; Sutton, MD (2010)
An exceptionally preserved new ostracod crustacean from the Silurian of Herefordshire, UK, represents only the third fully documented Palaeozoic ostracod with soft-part preservation. Appendages, gills, gut system, lateral compound eyes and even a medial eye with a Bellonci organ are preserved, allowing assignment of the fossil to a new genus and species of cylindroleberidid myodocope (Myodocopida, Cylindroleberididae). The Bellonci organ is recorded for the first time in fossil ostracods. The find also represents a rare occurrence of gills in fossil ostracods and confirms the earliest direct evidence of a respiratory-cum-circulatory system in the group. The species demonstrates remarkably conserved morphology within myodocopes over a period of 425 Myr. Its shell morphology more closely resembles several families of myodocopes other than the Cylindroleberididae, especially the Cypridinidae and Sarsiellidae, thus questioning the utility of the carapace alone in establishing the affinity of fossil ostracods.